Destabilizing Different Strengths of Fear Memories Requires Different Degrees of Prediction Error During Retrieval - Chen, Wei; Li, Junjiao; Xu, Liang; Zhao, Shaochen; Fan, Min; Zheng, Xifu (Frontiers in Behavioral Neuroscience, 2021)
Reactivation of consolidated memory can induce a labile period, in which the memory might be susceptible to change and need reconsolidation. Prediction error (PE) has been recognized as a necessary boundary condition for memory destabilization, and stronger memories are resistant to destabilization. This study investigated whether different strengths of conditioned fear memories require different degrees of PE during memory reactivation in order for the memories to become destabilized. Here we assessed the fear-potentiated startle and skin conductance response, used the post-retrieval extinction procedure. A violation of expectancy (PE) was induced during retrieval to reactivate enhanced (unpredictable-shock) or ordinary (predictable-shock) fear memories that were established the day before. Results showed that a PE retrieval before extinction can prevent the return of predictable-shock fear memory, but cannot prevent the return of unpredictable-shock fear memory, indicating that single PE is insufficient to destabilize enhanced fear memory. Therefore, we further determined whether increasing the degree of PE could destabilize enhanced fear memory using different retrieval strategies (multiple PEs retrieval and unreinforced CS retrieval). We found that spontaneous recovery of enhanced fear memory was prevented in both retrieval strategies, but reinstatement was only prevented in the multiple PEs retrieval group, suggesting that a larger amount of PE is needed to destabilize enhanced fear memory. The findings suggest that behavioral updating during destabilization requires PE, and the degree of PE needed to induce memory destabilization during memory retrieval depends on the strength of fear memory. The study indicates that memory reconsolidation inference can be used to destabilize stronger memories, and the findings shed lights on the treatment of post-traumatic stress disorders and anxiety disorders.